The Role of Macro and Micro Factors in Determining Stock Price: Empirical Evidence of LQ 45 Index Companies - Sabijono, Harijanto; Murni, Sri; Trang, Irvan; Elim, Inggriani; Mangantar, Maryam (Archives of Business Research, 2023)
This study aims to determine and analyze the influence of Profitability, Capital Structure, Exchange Rates and Interest Rates on Investment Risk and their effect on LQ 45 Index Stock Prices. The analysis was conducted on 25 LQ 45 index companies on the Indonesia Stock Exchange (IDX) using report data financial year 2012 to 2020. This study uses an explanatory design using secondary data in the form of JCI, Stock Return, Stock prices and financial report data obtained from LQ 45 Index Companies on the Indonesian Stock Exchange, as well as interest rates and exchange rates sourced from Bank Indonesia and BPS. Samples were taken by purposive sampling of 25 companies for 9 years of observation, using path analysis. The results of the study state that Profitability has no significant effect on Investment Risk, Capital Structure has a significant effect on Investment Risk, Exchange Rates have a positive and significant effect on Investment Risk, Interest Rates have no significant effect on Investment Risk However, Capital Structure has an indirect and significant effect on Stock Price through Investment Risk as an intervening variable. Profitability has a significant positive effect on stock prices, investment risk as an intervening variable between profitability and stock prices indirectly has no significant effect. Capital structure has no significant effect on stock prices, investment risk as an intervening variable between capital structure and stock prices indirectly has no significant effect. Exchange Rate has no significant effect on Stock Price, Investment Risk as an intervening variable between Exchange Rate and Stock Price indirectly has no significant effect. Interest Rates do not have a significant effect on Stock Prices, Investment Risk as an intervening variable between Interest Rates and Stock Prices indirectly does not have a significant effect. Investment risk has no significant effect on stock prices.